1999
DOI: 10.1111/j.1151-2916.1999.tb01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Crystallization of Forsterite and Orthoenstatite

Abstract: MgO-SiO 2 precursor gels were prepared by mixing tetramethoxysilane (TMOS) or tetraethoxysilane (TEOS), H 2 O, and magnesium metal in methanol. Forsterite (Mg 2 SiO 4 ) and orthoenstatite (MgSiO 3 ) were crystallized from their precursors at temperatures as low as 500°and 700°C, respectively. The chemical compositions of the crystallized phases were richer in MgO content than those of the starting materials. Inductively coupled plasma analysis showed that an amorphous SiO 2 -rich phase was present, together wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 12 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…It belongs to the group of olivine. Like clinoenstatite, with the formula MgSiO 3 , forsterite has an extremely low electrical conductivity [1]. This makes forsterite ceramics an ideal substrate material for electronics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It belongs to the group of olivine. Like clinoenstatite, with the formula MgSiO 3 , forsterite has an extremely low electrical conductivity [1]. This makes forsterite ceramics an ideal substrate material for electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Forsterite has been synthesized by solid state reaction of MgO and SiO 2 [5] or bauxite and MgCO 3 [6], and by various sol-gel methods [1,7,8] which include a H 2 O 2 assisted process [9].…”
Section: Introductionmentioning
confidence: 99%
“…Forsterite is known to be an insulator at high frequencies; its precursor powder and xerogel have been synthesized via the sol-gel method. [7][8][9][10] A previous systematic study 11 has shown that acetate anion behaves as a ligand and modifies the molecular structure of the gel, playing an important role in the formation of spinnability when the forsterite precursor solution is hydrolyzed with an adequate amount of acetic acid. Factors affecting the properties or type of the hydrolyzed molecular structure have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It belongs to the group of olivine. Like clinoenstatite, with the formula MgSiO 3 , forsterite has an extremely low electrical conductivity [4]. This makes forsterite ceramics an ideal substrate material for electronics.…”
Section: Introductionmentioning
confidence: 99%